Peripheral blood immunophenotyping in a large cohort of patients with Shwachman–Diamond syndrome. Issue 5 (2nd January 2019) - Bezzerri, Valentino; Vella, Antonio; Gennaro, Gianfranco Di; Ortolani, Riccardo; Nicolis, Elena; Cesaro, Simone; Fabrizzi, Benedetta; Bronte, Vincenzo; Corey, Seth J.; Cipolli, Marco
Abstract: Shwachman–Diamond syndrome (SDS) is one of the more common inherited bone marrow failure syndromes, characterized by neutropenia, occasional thrombocytopenia, and anemia. Bone marrow evaluation reveals an increased number of monocytes and mature B cells along with decreased granulocytes. However, little is known about the subpopulations of peripheral blood cells, and few previous publications have been based on a small number of patients. Here, we report a comprehensive immunophenotypic analysis from a cohort of 37 SDS patients who display impairment mostly in the myeloid compartment with a deficiency also in the number of B cells and CD4/CD8 double‐negative T cells.